Olive Oil Tourism Experience (OOTE): A Systematic Literature Review (SLR) - Bebiana Monteiro; Josefina Salvado (Via@)
This study aims to provide current and organized insights on Olive Oil Tourism Experience (OOTE) as an important food heritage. A systematic literature review (SLR) methodology by focusing on SCOPUS database was performed by systematically gathering the literature over 85 papers and coded according to categories such as author, year, article title, name of journal, perspective (S-supply, D-demand, R-Residents, ST-Stakeholders, T-Territory), main Issue, territory, goals, methodology and results. The key findings of this review reveal that no universal set of items, attributes or indicators to measure the OOTE exists; a lack of studies that address the relationship between Olive Oil Tourism and experience and between destination image, tourism experience, communities’ integration and synergies between other patrimonies (as wine). Future studies should consider complementing the tourism supply, demand and stakeholders’ side to avoid a “strategic drift” of OOTE concepts, perceptions, experiences and practices.